Mode of action for gastroprotective activity of Muntingia calabura L. leaves in rats - Balan, Tavamani (2016)
Gastric ulcer is one of the most common gastrointestinal disorders. As current antiulcer treatments are associated with wide range of side effects, there is a need to discover an effective and safer new antiulcer agent. Muntingia calabura L. (family Muntingiaceae), known as Jamaican cherry or kerukup siam has been employed traditionally to treat various ailments including gastrointestinal disorders. The traditional use of M. calabura and its potential antioxidant properties lead to the present research with the hope of finding an effective gastroprotective agent. The present study aimed to investigate the antiulcer activity of M. calabura methanolic leaves extract (MEMC) and its fractions using rat models, determine the underlying mechanism(s) of action and identify the phytochemical constituents present in the plant. Acute toxicity study was conducted using a single oral dose of 2000 mg/kg MEMC. The antiulcer activity of MEMC was evaluated in ethanol- and indomethacin-induced gastric ulcer rat models. The rats were administered 8% Tween 80, 100 mg/kg ranitidine, and MEMC (doses 25-500 mg/kg) orally for seven days, followed by ulcer induction using absolute ethanol (5 mL/kg) or indomethacin (100 mg/kg). The rats were euthanized; macroscopic and histological observations of the stomach were done. Fractionation of MEMC yielded petroleum ether (PEF), ethyl acetate (EAF) and aqueous (AQF) fractions. Their antiulcer property was investigated using ethanol-induced gastric ulceration as described above. MEMC and its fractions were subjected to antioxidant and anti-inflammatory studies including superoxide and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, oxygen radical absorbance capacity (ORAC), total phenolic content (TPC), inhibition of nitric oxide (NO), lipoxygenase (LOX) and xanthine oxidase (XO) activity. Evaluation of gastric content and quantification of mucus were carried out in pylorus-ligated model. Possible involvement of endogenous NO and sulfhydryl (SH) compounds was determined in animals pre-treated with NGnitro- L-arginine methyl esters (L-NAME) or N-ethylmaleimide (NEM) prior to MEMC or EAF treatment. Superoxide dismutase (SOD), gluthathione (GSH), catalase (CAT), malondialdehyde (MDA), prostaglandin E2 (PGE2) and NO level in the stomach tissue homogenate treated with EAF was determined. Phytochemical screening and High Performance Liquid Chromatography (HPLC) analysis was conducted on MEMC, PEF and EAF. EAF was further subjected to Ultra-high-Performance Liquid Chromatography-Electrospray Ionization (UHPLC-ESI) analysis. The LD50 of MEMC was >2000 mg/kg. MEMC exerted significant (p<0.001) gastroprotection in both the ulcer models. PEF and EAF significantly (p<0.001) attenuated the ethanol-induced gastric lesions. MEMC and its fractions showed high antioxidant and anti-inflammatory activities. MEMC and EAF significantly (p<0.01) reduced volume of gastric content and increased the mucus production. Pre-treatment with L-NAME or NEM reversed the gastroprotection of MEMC and EAF. EAF markedly ameliorated the SOD, GSH, CAT, PGE2 and NO level while reducing MDA level. HPLC profiling showed the presence of quercetin and gallic acid in MEMC, PEF and EAF. UHPLC-ESI confirmed the presence of these compounds in EAF. In conclusion, MEMC and EAF exert significant antiulcer activity. The underlying gastroprotective mechanisms of MEMC and EAF could be associated with the antioxidant, anti-inflammatory, antisecretory, participation of mucus, antiperoxidative, modulation of NO and SH compounds and presence of flavonoids and phenols.